Analisis Pendekatan Kegunaan Keputusan Untuk Laporan Keuangan Pada Perusahaan (Literature Review) - Muhammaddin, Novandra; Suseno, Bayu; Uzliawati, Lia (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This paper explores the financial reporting practices within a corporation. The management is capable of overseeing each business development by engaging in the preparation of records, bookkeeping, and reports detailing all ongoing business activities. In correlation with this, there exists an appropriate tool for assessing and monitoring a company's financial performance within a specific timeframe – namely, financial reports utilizing a decision-use approach. To gain a swift comprehension of this concept, it is imperative to delve into other economic and financial theories. As an accountant, it is essential to comprehend how to enhance the usefulness of financial statements and gain insight into the meaning of